Gisi Marimas: Giat Literasi Dengan Makan Bergizi Dan Minum Yang Sehat Bersama Perpustakaan Cemerlang Desa Watualang - Hanifah Hikmawati (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract; This article discusses the importance of eating nutritious food and drinking healthy which is echoed by the Watualang Village Cemerlang Library to the community. Cemerlang Library is a library transformation based on social inclusion that focuses on community welfare and as a problem solver for phenomena that occur in society. One of the breakthroughs of social inclusion is the Cemerlang library of Watualang village in the form of the "Gisi Marimas" activity which stands for "Active Literacy by Eating Nutritious and Drinking Healthy". The research method is in the form of descriptive qualitative, by describing words and statements as well as evaluating validity through cross-checking of information sources. The results of the research show that the Watualang village Cemerlang library intensively organizes progressive activities in the form of food processing practicum activities. The results of Gisi Marimas can support the body's source of nutrition and energy. Regular consumption of healthy food can also provide many benefits, ranging from boosting immunity, strengthening muscles and bones, reducing the risk of chronic disease, improving digestion, and maintaining ideal body weight. Keywords; Literacy, Nutritious Food, Healthy Drinks, Brilliant Library of Watualang Village, Social Inclusion